AN ANALYSIS ON THE SECOND SEMESTER STUDENTS’ ABILITY IN UNDERSTANDING PAST SIMPLE SENTENCES AT THE ENGLISH EDUCATION DEPARTMENT OF STKIP INSAN MADANI AIRMOLEK - Loly - Novita; Gusparia Gusparia; Muhammad Sabri (Politeknik Negeri Bengkalis, 2021)
A descriptive qualitative method was used in this research. It aimed to find out the students’ ability in understanding Past Simple. The instrument of the research to gather the data was in the form of written test which was delivered to the the second semester students. They are asked to do the test of verbal sentence, nominal sentence and irregular or regular verb use. The test was designed based on the relevant literature review and the authors’ observation during the teaching learning process which took time especially when the material of the Past Simple was explained. For the test as a whole, there were only 3 students (12.5%) who had high category level of Past Simple understanding. Meanwhile, 10 students’ ability in understanding Past Simple (41.7%) was in the middle category. There were 11 students (45.83%) whose ability belonged to the low category. In short, the students’ ability in understanding Past Simple was still low. The research findings give some points of view for a lecturer to remember that he needs to have various teaching techniques to get her students’ attention to learn and practice more about the use of tense, especially Past Tense. The lecturer can also use interesting audio visual teaching media so that the students get more interest to acquire the rules